SOCIAL CAPITAL ON COMMUNITY DEVELOPMENT: SURVEY IN WEST JAVA INDONESIA - Dulkiah, Moh. (GoAcademica Research dan Publishing, 2025)
This study analyzes the influence of social capital on community development, focusing on the role of university students in community service initiatives. Using a Systematic Literature Review (SLR) approach and Path Analysis, the VOSviewer analysis highlights that key concepts related to social capital, such as